2021
DOI: 10.1111/ctr.14534
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and predictive functional profiles on metagenomic 16S rRNA data of liver transplant recipients: A longitudinal study

Abstract: Long-term survival after Liver Transplantation (LT) is often compromised by infectious and metabolic complications. We aimed to delineate alterations in intestinal microbiome (IM) over time that could contribute to medical complications compromising long-term survival following LT. Fecal samples from LT recipients were collected at 3 months (3 M) and 6 months (6 M) post-LT. The bacterial DNA was extracted using E.Z.N.A. Stool DNA Kit and 16S rRNA gene sequencing at V4 hypervariable region was performed. DADA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The incidence of NAFLD has increased significantly in recent years and has become a major cause of chronic liver disease worldwide, affecting human health adversely. [ 9 , 10 ] In view of the gut-liver axis concept, gut microbiota has emerged as a crucial topic in liver disease research and demonstrated its impact on the occurrence and development of chronic liver disease. Despite advances in the gut microbiota macrogenomics, the characteristics of the NAFLD gut microbiota and its metabolites have not been fully defined.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of NAFLD has increased significantly in recent years and has become a major cause of chronic liver disease worldwide, affecting human health adversely. [ 9 , 10 ] In view of the gut-liver axis concept, gut microbiota has emerged as a crucial topic in liver disease research and demonstrated its impact on the occurrence and development of chronic liver disease. Despite advances in the gut microbiota macrogenomics, the characteristics of the NAFLD gut microbiota and its metabolites have not been fully defined.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal DNA was extracted from stool samples using an E.Z.N.A. ® Stool DNA Kit (Omega Bio-Tek, USA) 35 following the manufacturer's guidelines. Specific primers (F341: ACTCCTACG GGRSGCAGCAG, R806: GGACTACVVGGGTATCTAATC) with barcodes targeting the V3-V4 hypervariable region of the 16S rRNA gene were used for PCR amplification in triplicate.…”
Section: S Rrna Sequencingmentioning
confidence: 99%
“…After excluding the publications not complying with inclusion criteria, 86 records were considered suitable for full-text analysis. After reading these papers and examining their content the two reviewers identified 50 papers [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ,…”
Section: Resultsmentioning
confidence: 99%
“…The main findings of the selected studies were summarized in a narrative form in the text of the article and in two tables, the first ( Table 1 ) concerning the papers on the effect of the intestinal microbiota on cIMDs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], and the second ( Table 2 ) concerning the papers on effect of cIMDs on intestinal microbiota [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ,…”
Section: Methodsmentioning
confidence: 99%